Being Present in Action: A Theoretical Model About the “Interlocking” Between Intentions and Environmental Affordances - Triberti, Stefano; Riva, Giuseppe (Frontiers in Psychology, 2016)
Recent neuropsychological evidence suggest that a key role in linking perceptions and intentions is played by sense of presence. Despite this phenomenon having been studied primarily in the field of virtual reality (conceived as the illusion of being in the virtual space), recent research highlighted that it is a fundamental feature of everyday experience. Specifically, the function of presence as a cognitive process is to locate the Self in a physical space or situation, based on the perceived possibility to act in it; so, the variations in sense of presence allow one to continuously adapt his own action to the external environment. Indeed intentions, as the cognitive antecedents of action, are not static representations of the desired outcomes, but dynamic processes able to adjust their own representational content according to the opportunities/restrictions emerging in the environment. Focusing on the peculiar context of action mediated by interactive technologies, we here propose a theoretical model showing how each level of an intentional hierarchy (future-directed; present directed; and motor intentions) can “interlock” with environmental affordances in order to promote a continuous stream of action and activity.